Isolation and some properties of tyrosinase from Symplectoteuthis oualaniensis - Thu, Nguyen Xuan; Lan Oanh, Le Thi; Dinh, Tran Canh (Academia Journal of Biology, 2014)
Tyrosinase is the key enzim in the reaction chain of melanin biosynthesis, which causes the enzymatic darkening of S. oualaniensis after being caught. We have extracted and investigated some agents, which were used to inhibit the activity of tyrosinase extracted from S. oualaniensis. The results showed that tyrosinase from S. oualaniensis had the optimal pH from 6.5 - 7.0. When being temperature treated for 5 minutes at 70 - 80oC, its activity was 65 - 30% of the original and at 100oC, it was inactive. Ascorbic acid, NaHSO3, EDTA and extracts of ST and NS were inhibitors of S. oualaniensis tyrosinase. Treating for 5 minutes, 10 mM ascorbic acid inhibited 68% and EDTA - 97%, 100 mM of NaHSO3 inhibited 57%, ST 73% and NS 33% S. oualaniensis tyrosinase activity.